Bibliometric Computation Mapping Publication Analysis in Sports Psychology using VOSviewer - Mona Fiametta Febrianty; Komarudin; Yusuf Hidayat; Dede Rohmat Nurjaya (Universitas Negeri Semarang, 2024)
In the field of sports coaching, research urgently needed that is closely related to achievement. Specifically, in the field of sports psychology, there is still a great need for research that specifically examines ideas that can be used as input for those who need them. The purpose of this study is to examine developments regarding sports psychology research, especially aspects of psychology that are currently developing rapidly through a bibliometric approach using a computerized mapping analysis application using VOSviewer. Apart from that, this research hopes to identify existing research trends in the field of sports psychology. Various article data obtained were sourced from Google Scholar using the Publish or Perish Reference Manager application. The keywords used to guide the search process in this research are “Psychological Aspects on Athletes”. During the search, the author found 988 articles relevant to the keyword. The articles obtained came from a span of 10 years, namely 2012-2022, and came from various journals and publishers. If explained one by one the published articles related to the psychological aspects of athletes from year to year will be obtained as follows: 55 articles in 2012, 62 articles in 2013, 69 articles in 2014, 73 articles in 2015, 73 articles in 2016, 74 articles in 2017, 89 articles in 2018, 119 articles in 2019, 140 articles in 2020, 132 articles in 2021 and 102 articles in 2022. Judging from the data, it can be seen that there has been an increase and decrease from year to year and we checked all of this using VOSviewer. The results of this study will help future researchers regarding sports psychology, especially aspects of psychology in sports, in finding sources, studies, and theories that are relevant to their research. However, this research still has limitations in using the application, so it is recommended to use other applications that make it possible to obtain further results.